Alignment of buccally displaced canines following premolar extractions: archwtre or natural alignment? - Lew Kenneth (Sciendo, 1989)
The alignment times of buccally displaced maxillary canines following first premolar extractions were studied in 2 groups. The control group (n=28) comprised of cases where no appliances were used while the experimental group (n=28) had Begg brackets bonded on the upper teeth in conjunction with Sentalloy archwire. The imbrication indices (I.I.) of all canines were recorded for both groups prior to extraction and every 5 days after extractions until the canines aligned. The results indicated that there was no significant difference in the alignment rate at 30 days and 60 days between the 2 groups. However, the alignment rates at 90 and 120 days were both significantly faster in the experimental compared to the control group (p < 001). While the alignment rates at 30, 60, 90 and 120 days in the experimental group followed a plateaued curve, the alignment rates in the control group followed a cusped curve. The results indicated that a 2 months self-alignment period following premolar extractions would be justified in most cases before banding.